EFFORTS TO IMPROVE STUDENTS WRITING POETRY SKILLS USING THE IMAGINATIVE MODEL SHORT VIDEO ON SOCIAL MEDIA (Action Research Class X MAN 2 Bandung Regency) - Hana Fatimah, - (2022)
This research is motivated by the difficulty of students in class X MIPA 4 MAN 2 Bandung Regency in writing poetry. The problems of writing poetry for students of class X MIPA 4 MAN 2 Bandung Regency can be classified into several things (1) the ability to choose diction that is still cliche, (2) lack of ideas, and (3) interesting images. For this reason, the study aims to improve student's poetry writing skills by solving these problems using the Class Room Action Research method through a qualitative descriptive approach. The data sources in this study were students of class X MIPA 4 MAN 2 Bandung Regency for the academic year 2021/2022 a total of 32 people. The instruments used are observation, interviews, questionnaires, field nontes, and tests. The data analysis technique in this study used qualitative descriptive. The results of this study indicate that there is an increase in student's writing poetry skills after a two-cycle guidance process that includes four stages. In the first cycle, the research was conducted in three stages. Then, in the second cycle this research was carried out in one stage. The increase in writing poetry occurred from cycle one to cycle two. Students experienced an increase in aspects of originality of works, aspects of poetry structure, aspects of depth of meaning, and aspects of cohesiveness. By using an imaginative learning model assisted by short media, there is a process of acceptance of understanding that can make it easy for students to practice writing poetry correctly. In addition, the application of the learning model used in learning to writing poetry can stimulate students to think creatively and imaginatively.